Epidemiological, clinical, and genomic landscape of coccidioidomycosis in northeastern Brazil - Eulálio, Kelsen Dantas; Kollath, Daniel R.; Martins, Liline Maria Soares; Filho, Antonio de Deus; Cavalcanti, Maria do Amparo Salmito; Moreira, Lucas Machado; Tenório, Bernardo Guerra; Alves, Lucas Gomes de Brito; Yamauchi, Danielle [UNESP]; Barrozo, Ligia Vizeu; Thompson III, George R.; Nacher, Mathieu; et al. (Springer Nature, 2024)
Coccidioidomycosis, listed as a priority mycosis by the WHO, is endemic in the United States but often overlooked in Central and South America. Employing a multi-institutional approach, we investigate how disease characteristics, pathogen genetic variation, and environmental factors impact coccidioidomycosis epidemiology and outcomes in South America. We identified 292 cases (1978–2021) and 42 outbreaks in Piauí and Maranhão states, Brazil, the largest series outside the US/Mexico epidemic zone. The male-to-female ratio was 57.4:1 and the most common activity was armadillo hunting (91.1%) 4 to 30 days before symptom onset. Most patients (92.8%) exhibited typical acute pulmonary disease, with cough (93%), fever (90%), and chest pain (77%) as predominant symptoms. The case fatality rate was 8%. Our negative binomial regression model indicates that reduced precipitation levels in the current (p = 0.015) and preceding year (p = 0.001) predict heightened incidence. Unlike other hotspots, acidic soil characterizes this region. Brazilian strains differ genomically from other C. posadasii lineages. Northeastern Brazil presents a distinctive coccidioidomycosis profile, with armadillo hunters facing elevated risks. Low annual rainfall emerges as a key factor in increasing cases. A unique C. posadasii lineage in Brazil suggests potential differences in environmental, virulence, and/or pathogenesis traits compared to other Coccidioides genotypes.